Women’s parliamentary representation in the Czech Republic: does preference voting matter? - Stegmaier, Mary; Tosun, Jale; Vlachová, Klára (East European politics and societies, 2014)
The U-shaped trajectory of women’s parliamentary representation in Central and Eastern Europe over the post-communist era has generated interest among scholars ...
First published July 24, 2013
Gesehen am 22.10.2020